Універсальна біотехнологія знешкодження токсичних органічних відходів і металів з отриманням цінних продуктів (за матеріалами наукового повідомлення на засіданні Президії НАН України 28 грудня 2022 р.) - Говоруха, В.М. (Вісник НАН України, 2023)
Доповідь присвячено дослідженню закономірностей взаємодії мікроорганізмів з органічними відходами і токсичними металами та визначенню способів їх знешкодження. Розглянуто шляхи оптимізації та підвищення ефективності цього процесу. Запропоновано підхід до створення універсальної біотехнології одночасного зброджування багатокомпонентних органічних
відходів та видалення розчинних токсичних металів з отриманням цінних
продуктів: молекулярного водню, метану, твердого палива, біодобрива,
концентрату металів та очищеної води. The report deals with the study of the patterns of microorganisms interaction with organic waste and toxic metals, the
determination of pathways for their treatment, optimization of the process and increasing its efficiency, as well as the
development of the approach for the universal biotechnology for the simultaneous fermentation of multicomponent organic
waste and the removal of soluble toxic metals with obtaining of a number of valuable products: molecular hydrogen,
methane, solid fuel, biofertilizer, metal concentrate and purified water.
The approach is based on the thermodynamic prediction to optimize waste fermentation. It consists of the following
principles: all microbial metabolism pathways are permissible only in H2O thermodynamic stability zone, in the range
of Ео’ = –414…+814 mV; the optimal conditions for hydrogen and methane fermentation are pH = 7.0 under anaerobic
conditions, i.e. at potential of –414 mV. Microbial metabolism regulation is necessary to achieve high efficiency of
fermentation process. We have theoretically substantiated and experimentally confirmed 10 optimized fermentation
parameters, such as pH (6.5—7.4), Eh (–350…–414 mV), particle size (5—20 mm), etc. The use of granular microbial
preparation and the regulation of these parameters provided the significant increase in the speed and efficiency of
hydrogen fermentation of waste. Using spatial succession, i.e. the change of ecosystem components, we have achieved
complete purification of filtrate from soluble organic compounds formed after fermentation.
The thermodynamic prediction provided an effective combination of organic waste degradation and metal-containing
sewage treatment by obligate anaerobic microorganisms. The reduction of chromates to insoluble Cr(III) hydroxide by
hydrogen-synthesizing anaerobic bacteria during hydrogen fermentation of model waste (potatoes) was shown to be
possible even at Cr(VI) concentration equal to 1000 mg/L.
Thus, the thermodynamic prediction method, the microbial metabolism regulation, the application of microbial
preparations and spatial succession provided fast and effective treatment of a wide range of solid and liquid organic
waste, as well as metal-containing sewage with obtaining of valuable products.